Soil exchangeable cations and acidity components in different cropping systems for onion - Muetanene, Belo Afonso; Luiz Mafra, Álvaro; Adriano Albuquerque, Jackson; Souza Brito, Erbesson; Alassane, Daibou; Peternelli, Luiz Alexandre; Ossifo, Momate Emate (JOURNAL OF ADVANCES IN AGRICULTURE, 2022)
This study aimed to evaluate K, Ca, Mg, Al concentrations and active acidity (pH-H2O) in different cropping systems for onion. The study was conducted on a Humic Dystrudept in Ituporanga, Santa Catarina state, Brazil, where eight different cropping systems for onion were evaluated, namely: T1: maize-onion succession, T2: common vetch-maize/rye+fodder raddish-onion-maize/rye+fodder raddish-common bean, T3: rye-onion-maize/black oat-maize, T4: onion-velvet bean succession, T5: rye-onion-millet/black oat-onion-millet, T6: rye-onion-velvet bean succession, T7: onion-velvet bean+millet+sunflower succession, from T1 to T7 were conducted under no tillage system (NTS), T8, T8: maize-onion succession, was conducted under conventional tillage system. We used the randomized complete block design, with 5 replications. All the chemical samples were collected and evaluated at the 0-5, 5-10 and 10-20 cm soil layers. We observed that the different cropping systems were similar in terms of Ca, Mg and K concentrations in all the soil layers, significant differences were only found for exchangeable Al concentrations at the 0-5 cm layer. More time is needed to observe better the performance of the treatments since their effect on the soil depends a lot on the time of implantation.